Telemonitoring Detak Jantung Pasien Berbasis Internet untuk Implementasi pada Sistem Telemedika - Arifin, Rosyid; , Dr. Ratnasari Nur Rohmah, ST, MT (2016)
Telemonitoring is a method of monitoring a patient's condition in which the patient and the doctor are not in the same location. Telemonitoring is one of telemedicine field, the science field that using multiple sciences to improve the remote health care services. One patient's medical data that needs to be monitored is the patient's heartbeat. The heartbeats measurement tools available today requires that the doctor and the patient are in the same location. This requiremets limits the tool and becomes a problem when monitoring should be done regularly, while a meeting between doctors and patients in one place can not be done. This study developed a remote heart rate monitoring devices for Telemonitoring purposes. The data transfer on this instrument is using email to send the data after the patient's data obtained. The system consists of pulsesensor for detecting the heartbeat, Arduino Uno for signals processing, and Ethernet shield for data transmission via the internet. This equipment also use the computer to process the data delivery orders via email. Testing on device's performance shows that the device can be used as Telemonitoring equipment due to its ability to transmit patient's data via email. The device shows good accuracy with the best accuracy rate was achieved in the measurement of slowrate heart beat with a relative error of 1.2% compared to available oxymeter equipment. In the tests of medium and fast heartbeat rate, the device shows relative error measurements of 2.7%. These results gives chalenge for further research to improve the device's accuracy, especially in measuring the heart beat rate at medium dan fast rate. Keywords: Telemedicine, heart beat rate, Arduino, email.